Graded RhoA GTPase Expression in Treg Cells Distinguishes Tumor Immunity From Autoimmunity - Kalim, Khalid W.; Yang, Jun-Qi; Modur, Vishnu; Nguyen, Phuong; Li, Yuan; Zheng, Yi; Guo, Fukun (Frontiers in Immunology, 2021)
RhoA of the Rho GTPase family is prenylated at its C-terminus. Prenylation of RhoA has been shown to control T helper 17 (Th17) cell-mediated colitis. By characterizing T cell-specific RhoA conditional knockout mice, we have recently shown that RhoA is required for Th2 and Th17 cell differentiation and Th2/Th17 cell-mediated allergic airway inflammation. It remains unclear whether RhoA plays a cell-intrinsic role in regulatory T (Treg) cells that suppress effector T cells such as Th2/Th17 cells to maintain immune tolerance and to promote tumor immune evasion. Here we have generated Treg cell-specific RhoA-deficient mice. We found that homozygous RhoA deletion in Treg cells led to early, fatal systemic inflammatory disorders. The autoimmune responses came from an increase in activated CD4+ and CD8+ T cells and in effector T cells including Th17, Th1 and Th2 cells. The immune activation was due to impaired Treg cell homeostasis and increased Treg cell plasticity. Interestingly, heterozygous RhoA deletion in Treg cells did not affect Treg cell homeostasis nor cause systemic autoimmunity but induced Treg cell plasticity and an increase in effector T cells. Importantly, heterozygous RhoA deletion significantly inhibited tumor growth, which was associated with tumor-infiltrating Treg cell plasticity and increased tumor-infiltrating effector T cells. Collectively, our findings suggest that graded RhoA expression in Treg cells distinguishes tumor immunity from autoimmunity and that rational targeting of RhoA in Treg cells may trigger anti-tumor T cell immunity without causing autoimmune responses.